2000
DOI: 10.1046/j.1365-2133.2000.03660.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of desmoglein 1 autoantibodies in pemphigus vulgaris: racial differences in frequency and the association with a more severe phenotype

Abstract: These data suggest that the presence of Dsg1 antibodies is predictive of a potentially more severe disease and that genetic factors may determine the Dsg antibody profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
80
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 25 publications
12
80
1
2
Order By: Relevance
“…Pesticide exposure 9. Pregnant females 10 The demonstration by Beutner and Jordan of serum antibodies directed against the intercellular substance of stratified squamous epithelium was the first in a series of findings that suggested that PV may be an auto immune disease. 11 Pemphigus vulgaris is an autoimmune disorder in which there is deposition of mainly IgG class antibodies intracellularly, as well as damage to desmosomes by antibodies directed against the extracellular domains of cadherin-type epithelial cell adhesion molecules, particularly desmoglein 3.…”
Section: Etio-pathogenesismentioning
confidence: 99%
“…Pesticide exposure 9. Pregnant females 10 The demonstration by Beutner and Jordan of serum antibodies directed against the intercellular substance of stratified squamous epithelium was the first in a series of findings that suggested that PV may be an auto immune disease. 11 Pemphigus vulgaris is an autoimmune disorder in which there is deposition of mainly IgG class antibodies intracellularly, as well as damage to desmosomes by antibodies directed against the extracellular domains of cadherin-type epithelial cell adhesion molecules, particularly desmoglein 3.…”
Section: Etio-pathogenesismentioning
confidence: 99%
“…Pemfigus vulgariste anti-dsg 3 antikorlar› için tan›sal hassasiyet de¤iflik çal›flmalarda %85-100 olarak bildirilmektedir 7,[14][15][16] . Anti-dsg 1 antikorlar› ise pemfigus vulgarisli hastalarda de¤iflik oranlarda (%36-95 aras›nda) pozitif bulunmufltur 7,[15][16][17][18][19] . Bu çal›flmada klinik ve histopatolojik olarak pemfigus vulgaris tan›s› alm›fl olan 23 hastan›n hepsinde (%100) anti-dsg 3 antikorlar› pozitif saptan›rken; anti-dsg 1 pozitifli¤i ‹talya ve ‹ran'dan bildirilen oranlara yak›n (%73,9) bulunmufltur.…”
Section: Tart›flmaunclassified
“…Bu çal›flmada klinik ve histopatolojik olarak pemfigus vulgaris tan›s› alm›fl olan 23 hastan›n hepsinde (%100) anti-dsg 3 antikorlar› pozitif saptan›rken; anti-dsg 1 pozitifli¤i ‹talya ve ‹ran'dan bildirilen oranlara yak›n (%73,9) bulunmufltur. Farkl› çal›flmalarda anti-dsg 1 otoantikorlar›nda de¤iflik s›kl›kta pozitiflik saptanmas› klinik fenotiplerde görü-lebilen ›rksal farkl›l›klara ba¤lanmaktad›r 16,18 . Ülkemizde Akdeniz bölgesi'nde yap›lan bir çal›flmada olgular›n %87'sinde, ‹ran'-da ise %69,9 oran›nda mukokütanöz hastal›k bildirilmifltir 16,20 .…”
Section: Tart›flmaunclassified
“…In well developed disease almost all PV patients have circulating autoantibodies to Dsg3 Daneshpazhooh et al, 2007;Harman et al, 2000). More than 50% of PV patients also have Dsg 1 autoantibodies, the primary antigen of pemphigus foliaceus Daneshpazhooh et al, 2007;Harman et al, 2000). In some PV patients, the Dsg autoantibody profile correlates with the clinical manifestations (Daneshpazhooh et al, 2007;Endo et al, 2008c).…”
Section: Pemphigus Vulgarismentioning
confidence: 99%
“…The main target antigen of PV is desmoglein (Dsg) 3, a constituent of the extracellular region of desmosomes on keratinocytes (Amagai, 1999). In well developed disease almost all PV patients have circulating autoantibodies to Dsg3 Daneshpazhooh et al, 2007;Harman et al, 2000). More than 50% of PV patients also have Dsg 1 autoantibodies, the primary antigen of pemphigus foliaceus Daneshpazhooh et al, 2007;Harman et al, 2000).…”
Section: Pemphigus Vulgarismentioning
confidence: 99%